2007
DOI: 10.3390/i8060479
|View full text |Cite
|
Sign up to set email alerts
|

High-level Expression of Cecropin X in Escherichia coli

Abstract: Cecropin X is a short cationic peptide with a broad antibacterial and antitumor spectrum. Here, we report the production of a tumor necrosis factor (TNFα)-cecropin X fusion protein under the control of a temperature-inducible P R promoter in the bacterial expression vector pRC. During fermentation, we studied and optimized essential parameters including the type of host cells, medium, timing of induction, post-induction time and dissolved oxygen level. Using the suitable conditions in the fermentation, up to 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The fact that the glucose had little effect on VP1 protein production might be a result of catabolite repression. When a high concentration of glucose is used during E. coli cultivation, this abolishes catabolite repressor protein activity, which is how this protein senses the level of cyclic AMP in cells . Shen et al indicated that the presence of an additional carbon source, such as glycerol or glucose, might be beneficial to cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the glucose had little effect on VP1 protein production might be a result of catabolite repression. When a high concentration of glucose is used during E. coli cultivation, this abolishes catabolite repressor protein activity, which is how this protein senses the level of cyclic AMP in cells . Shen et al indicated that the presence of an additional carbon source, such as glycerol or glucose, might be beneficial to cell growth.…”
Section: Discussionmentioning
confidence: 99%
“…This cost can be reduced by using truncated derivatives and recombinant technology , although production in bacteria has been hindered by their anti-bacterial activity and proteolytic degradation (Bommarius et al, 2010). Good progress, however, has been reported using recombinant technology to scale up the production of cecropin for clinical trials (Shen et al, 2007;Chen et al, 2009b). Chen et al (2009b) obtained highly efficient expression of recombinant cecropin AD in B. subtilis yielding a pure, highly stable, peptide with potent antimicrobial activity at low MICs (minimal inhibitory concentrations) and applicable to industrial production.…”
Section: The Cost Of Developing Any New Antibiotic Drugmentioning
confidence: 98%
“…After optimizing the time and concentration of IPTG induction, the different medium cultures were investigated with (1) LB medium: 0.5% yeast extract, 1% peptone and 1% NaCl and 1.5% agar (Vulfson et al, 2001), (2) SOB medium culture: 2% peptone, 0.5% yeast extract, 10 mM NaCl, 2.5 mM KCl, 10 mM MgCl 2 and 10 mM MgSO4 (Shen et al, 2007), (3) SOC medium culture: 2% peptone, 0.5% yeast extract, 10 mM NaCl, 2.5 mM KCl, 10 mM MgCl 2 , 10 mM MgSO 4 and 20 mM glucose (Shen et al, 2007), (4) HSG medium culture: 1.49% glycerol, 0.7% yeast extract, 1.35% tryptone, 0.014% MgSO 4 .H 2 O, 0.15% KH 2 PO 4 , 0.23% K 2 HPO 4 and 0.5% (Miksch et al, 2008), and (6) TB medium culture: 1.2% peptone, 2.4% yeast extract, 72mM K 2 HPO 4 , 17mM KH 2 PO 4 and 0.4% glycerol (Shen et al, 2007) supplemented with 1% glucose and 100 μg/ml ampicillin. The culture was carried out on a rotation shaker with a speed of 200 rpm to an OD600 of 0.8.…”
Section: Expression Of Dhdps2 Proteinmentioning
confidence: 99%